2021
DOI: 10.1002/aenm.202102109
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Bottlebrush Polymeric Binders for High‐Mass‐Loading Cathodes in Lithium‐Ion Batteries

Abstract: high-voltage requirements. [1][2][3][4] However, the advancements of cathode active materials are overshadowed by the slow development of cathode binders, which should not be underestimated in terms of enabling practical cathode sheets. This issue becomes more stringent for the development of high-mass-loading cathode sheets, which have garnered considerable attention as a facile and scalable way to construct high-energy-density Li-ion batteries. [5][6][7] Major challenges facing the high-massloading cathode s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 57 publications
(62 reference statements)
0
29
0
Order By: Relevance
“…We also note that compounds other than Li 3 PO 4 may be used to complex or chelate dissolved Mn 2+ and reduce its effect on NMR spectra without causing HF consumption. The Mn-chelating abilities of various compounds (typically polymers) have been explored in electrolyte solutions with an aim toward reducing metal dissolution and deposition , and may be suitable for use in mitigating peak broadening, as long as 1 H signals from the chelating agent do not overlap with 1 H signals of interest.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that compounds other than Li 3 PO 4 may be used to complex or chelate dissolved Mn 2+ and reduce its effect on NMR spectra without causing HF consumption. The Mn-chelating abilities of various compounds (typically polymers) have been explored in electrolyte solutions with an aim toward reducing metal dissolution and deposition , and may be suitable for use in mitigating peak broadening, as long as 1 H signals from the chelating agent do not overlap with 1 H signals of interest.…”
Section: Discussionmentioning
confidence: 99%
“…As another example of functional additives, it has been recently reported that BBPs can act as a new class of cathode binders. 289 In this case, the amphiphilicity from hydrophobic PNB backbones and hydrophilic PAA sidechains can allow a uniform dispersion of cathode slurries. The prevalence of carboxylic acid groups in PAA sidechains provides a strong adhesion between the active materials and current collectors, leading to high-energy density Li-ion batteries.…”
Section: Discussionmentioning
confidence: 99%
“…The cycling stability was maintained at a binder content of 1 wt %, which is lower than that of typical batteries (10 wt %), and a high areal loading of 5.2 mA h cm –2 was achieved. This indicates that this binder allows for stable cycling, which is difficult to achieve with previously reported binders . In addition, polymers with electrochemical stability comparable to commercial binders, such as CMC, polyolefin, polyurethane, and polyimide, have been studied as binders.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that this binder allows for stable cycling, which is difficult to achieve with previously reported binders. 36 In addition, polymers with electrochemical stability comparable to commercial binders, such as CMC, polyolefin, polyurethane, and polyimide, have been studied as binders.…”
Section: Introductionmentioning
confidence: 99%